Structured gastroenterological intervention and improved outcome for patients with chronic gastrointestinal symptoms following pelvic radiotherapy. - Henson, Caroline C; Davidson, Susan E; Ang, Yeng; Babbs, Chris; Crampton, John; Kelly, Mark; Lal, Simon; Limdi, Jimmy K; Whatley, Greg; Swindell, Ric; Makin, Wendy; McLaughlin, John (Supportive Care in Cancer, 2013)
Purpose: Fifty percent of patients develop chronic gastrointestinal (GI) symptoms following pelvic radiotherapy that adversely affect quality of life. Fewer than 20 % are referred to a gastroenterologist. We aimed to determine if structured gastroenterological evaluation is of benefit to this patient group.Methods: Sixty patients with GI symptoms at ≥ 6 months after radical pelvic radiotherapy were identified prospectively from oncology clinics in this service evaluation. Those requiring urgent investigation were excluded. Patients were assessed at baseline using patient-reported questionnaires: inflammatory bowel disease questionnaire (IBDQ), Vaizey incontinence questionnaire, and the Common Terminology Criteria for Adverse Events (CTCAE) pelvis questionnaire. Participants were referred for gastroenterological evaluation using an algorithmic approach. Further assessments were made at 3 and 6 months.Results: Twenty men and 36 women with primary gynecological (31), urological (17), or lower GI (8) tumors were included (mean age, 58.5 years). Median time from radiotherapy to baseline assessment was 3.0 years. Multiple GI symptoms were reported (median, 8; range, 4-16) including frequency, urgency, loose stool, fecal incontinence, flatulence, bloating/distension, and rectal bleeding. Common diagnoses included radiation proctopathy, bile acid malabsorption, diverticulosis, and colonic polyps. Statistically significant improvements in all questionnaire scores between baseline and 6 months were found: IBDQ (p = 0.014), Vaizey (p < 0.0005), and CTCAE rectum-bowel subset (p = 0.001).Conclusions: Gastroenterological evaluation identifies significant, potentially treatable diagnoses in patients who develop chronic GI symptoms following pelvic radiotherapy. Some findings are incidental and unrelated to previous cancer treatment. Radiation-induced GI symptoms have historically been considered "untreatable." We report the first data to show that structured gastroenterological assessment has the potential to improve outcome by identifying diagnoses and facilitating focused treatment.